2021
DOI: 10.1111/ijn.12931
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a new normal—Hospital‐employed researchers' experiences during the COVID‐19 pandemic

Abstract: Background This study focuses on hospital‐employed researchers, a relatively new staff group. Their job descriptions vary, which may lead to lack of clarity or preparedness regarding their roles and core tasks during a crisis such as COVID‐19. Aim The aim of this study was to explore hospital‐employed healthcare researchers' experiences of work during the COVID‐19 pandemic. Design A qualitative design based on Graneheim and Lundman's latent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…(51) Staff who were considered non-essential such as clinical researchers and research assistants, were asked to pause their research, and join the frontline if able, in an attempt to lessen the burden on clinicians. (7) Research assistants are considered vital members of the team, especially in larger clinical trials, to ensure projects meet their deadlines. With hospitals recommending cancellation of non-essential outpatient clinic appointments, combined with research assistants being asked to avoid clinical spaces, and clinical researchers having to work on the frontline, it is understandable that a number of studies in our review reported delays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(51) Staff who were considered non-essential such as clinical researchers and research assistants, were asked to pause their research, and join the frontline if able, in an attempt to lessen the burden on clinicians. (7) Research assistants are considered vital members of the team, especially in larger clinical trials, to ensure projects meet their deadlines. With hospitals recommending cancellation of non-essential outpatient clinic appointments, combined with research assistants being asked to avoid clinical spaces, and clinical researchers having to work on the frontline, it is understandable that a number of studies in our review reported delays.…”
Section: Discussionmentioning
confidence: 99%
“…(6) Experienced hospital researchers have reported di culties conducting research during the COVID-19 pandemic. (7) Despite a signi cant amount of research published regarding the COVID-19 pandemic and its impact on healthcare workers, relatively less attention has been given to the impact of the pandemic on research and researchers, and even less so within Australia.…”
Section: Introductionmentioning
confidence: 99%
“…This cross‐sectional study draws on data from a larger study titled ‘Frontline’. Frontline is a study investigating the experiences of health care professionals, managers and hospital employed researchers during the COVID‐19 pandemic in order to generate recommendations on how to improve communication, cooperation and management in a future health care crisis (Berthelsen et al, 2021 ; Hølge‐Hazelton, Kjerholt, et al, 2021a ; Hølge‐Hazelton, Kjerholt, et al, 2021b ; Hølge‐Hazelton, Rosted, et al, 2021 ; Hølge‐Hazelton, Zacho Borre, et al, 2021 ). This study is a sub‐study of Frontline that looked specifically at ward managers' burnout symptoms, resilience and experiences with the supportive measures the hospital management launched in the wake of the second national lockdown (winter 2020–2021) at three time points during 2021.…”
Section: Methodsmentioning
confidence: 99%